2016
DOI: 10.1038/srep21569
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of the P56 mouse brain under large-deformation dynamic indentation

Abstract: The brain is a complex organ made up of many different functional and structural regions consisting of different types of cells such as neurons and glia, as well as complex anatomical geometries. It is hypothesized that the different regions of the brain exhibit significantly different mechanical properties, which may be attributed to the diversity of cells and anisotropy of neuronal fibers within individual brain regions. The regional dynamic mechanical properties of P56 mouse brain tissue in vitro and in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…S2). This suggests that over the range of the wire diameters studied, bulk brain tissue mechanics are generally homogeneous, consistent with previous studies on indentation into brain tissue 17,22 .…”
Section: Influence Of Microwire Diametersupporting
confidence: 89%
“…S2). This suggests that over the range of the wire diameters studied, bulk brain tissue mechanics are generally homogeneous, consistent with previous studies on indentation into brain tissue 17,22 .…”
Section: Influence Of Microwire Diametersupporting
confidence: 89%
“…2). This suggests that over the range of the wire diameters studied, bulk brain tissue mechanics are generally homogeneous, consistent with previous studies on indentation into brain tissue 20,32 .…”
Section: Influence Of Microwire Diametersupporting
confidence: 89%
“…In the absence of appropriate human tissue, animal tissue is used instead, and a porcine or rodent model is typically employed in these investigations 50 . Like human tissue, previous results in the literature have demonstrated that the mechanical properties of animal brain tissue are regionally dependent in the rat, mouse, and pig brains 13 16 , 21 . However, the answer as to which animal model is the most suitable surrogate remains moot.…”
Section: Discussionmentioning
confidence: 92%